A Novel Recessive RPGRIP1 Mutation Causing Leber Congenital Amaurosis - Abouzeid, H.; Othman, I. S.; Schorderet, D. F. (Klinische Monatsblätter für Augenheilkunde, 2016)
Background: Leber congenital amaurosis is an early-onset childhood severe retinal dystrophy, of significant genetic heterogeneity. RPGRIP1 is ubiquitously expressed, but mutations in RPGRIP1 lead to a retina-restricted phenotype, such as Leber congenital amaurosis and cone-rod dystrophy. Patient and Methods: We analysed a consanguineous family from Egypt in which one individual, a four-year-old girl, was affected with Leber congenital amaurosis. IROme, a proprietary enrichment system for retinal dystrophy genes, was applied and high throughput sequencing was performed. Results: Severe visual impairment was reported during infancy. The fundus of the affected patient exhibited disc pallor and attenuated vessels. Neurodevelopmental delay and brain atrophy in the CT scan were reported. Genomic sequencing identified a novel homozygous deletion, c.[420delG], in RPGRIP1. This mutation was not detected in 80 ethnically matched controls and has not been reported elsewhere. Conclusions: Identifying new mutations in Leber congenital amaurosis-related genes and their clinical manifestations can improve our understanding of the disease and could help to stratify the population for potential therapies.
Keywords: Leber congenital amaurosis; genetics; RPGRIP1; cone-rod dystrophy